BILATERAL ATROPHIC MACULOPATHY IN TWO SIBLINGS OF WOLFRAM SYNDROM - Tayyab Azeem Janjua (Army Medical College Rawalpindi, 2018)
Wolfram disease is a rare genetic disease which mainly presents as diabetes mellitus and optic atrophy. Presence of maculopathy in a case of wolfram disease is rarely reported in literature. We present here two cases/siblings with age of 12 and 14 years. They had diabetes mellitus, deafness and disc palor. Ocular examination also revealed atrophic maculopathy in both siblings, supported by depressed response on ERG. Assosiation of maculopathy with wolfram syndrome is rare and worth reporting.